Physik für ingenieure. - Hahn, Ulrich (De Gruyter Studium., 2015)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> The discipline of physics is an essential cornerstone to the education of engineers. It not only provides a basis for understanding technical applications, but also furnishes methods and strategies for acquiring new technical knowledge. This first volume presents mechanics, thermodynamics, oscillation, and waves.